Data underlying the research on GRACE constraints on Earth rheology of the Barents Sea and Fennoscandia ... - Rovira Navarro, Marc; van der Wal, W. Wouter; Barletta, V.A. Valentina; Root, B.C. Bart; Sørensen, Louise Sandberg (4TU.Centre for Research Data, 2019)
Data used in the manuscript "GRACE constraints on Earth rheology of the Barents Sea and Fennoscandia”. The dataset includes gravity disturbance rates derived form GRACE for these regions and gravity disturbance rates maps from an ensemble of GIA models corresponding different ice deglaciation chronologies and Earth rheology models. ...